2016
DOI: 10.3390/nu8110707
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Status and Risk of Cardiovascular Diseases and Type 2 Diabetes Mellitus—A Systematic Review of Prospective Cohort Studies

Abstract: Zinc is an essential trace element with proposed therapeutic effects in Type 2 diabetes mellitus (DM), however, the associations between zinc status and the prospective risks of cardiovascular diseases (CVD) and Type 2 DM have not been evaluated. The current systematic review aims to determine the relationships between zinc intake or plasma/serum zinc levels and prospective incidence of CVD and Type 2 DM. Fourteen papers describing prospective cohort studies were included, reporting either CVD (n = 91,708) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
47
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 50 publications
5
47
0
Order By: Relevance
“…In the present study, no significant difference was found between dietary zinc intake and CVD incidence, which is consistent with a systematic review of prospective cohort studies on the association between dietary zinc intake or serum zinc levels and the incidence of CVD (38). In contrast with our result, higher total dietary zinc intake (estimated by summing the zinc contribution of food items) was associated with a greater incidence of CVD in a large longitudinal study on Australian women.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, no significant difference was found between dietary zinc intake and CVD incidence, which is consistent with a systematic review of prospective cohort studies on the association between dietary zinc intake or serum zinc levels and the incidence of CVD (38). In contrast with our result, higher total dietary zinc intake (estimated by summing the zinc contribution of food items) was associated with a greater incidence of CVD in a large longitudinal study on Australian women.…”
Section: Discussionsupporting
confidence: 91%
“…Zinc is an essential trace element that is directly implicated in the physiology of glucose metabolism, participating in the synthesis, storage, secretion, action and translocation of insulin into the cells [1][2][3], as well as translocation of GLUT4 to the cell surface for glucose transport into the insulin responsive cells [4]. Disturbances in zinc homeostasis may play a role in the pathogenesis [5,6], pathophysiology [7][8][9] and control [10][11][12] of type 2 diabetes mellitus (T2DM). In addition, it has been observed that T2DM patients with a good glycemic control had a higher zinc status compared to those with poor glycemic control [13].…”
Section: Introductionmentioning
confidence: 99%
“…It works as co‐factor in various enzymes and proteins and possesses antioxidant, anti‐inflammatory and anti‐apoptotic properties . Multiple evidence has indicated the protective effects of zinc against several chronic diseases such as diabetes . Numerous in vitro and animal model studies have demonstrated the anti‐glycation impact of zinc …”
Section: Introductionmentioning
confidence: 99%
“…6,7 Multiple evidence has indicated the protective effects of zinc against several chronic diseases such as diabetes. 8,9 Numerous in vitro and animal model studies have demonstrated the anti-glycation impact of zinc. 10,11 Despite the large number of important researches, zinc has not been applied as a therapeutic intervention in humans in part due to the fact that information on its anti-glycation effects has not been yet summarized.…”
Section: Introductionmentioning
confidence: 99%